Macroeconomics, Agriculture, and Food Security - Díaz-Bonilla, Eugenio (2015)
IFPRI Policy Seminar “Macroeconomics, Agriculture & Food Security” on October 28, 2015. Presentation by Eugenio Diaz-Bonilla, IFPRI.